PO130 A case of neuromyelitis optica spectrum disease, necrotizing myositis and breast cancer. (1st December 2017) - Grant, Eleanor; Rose-Innes, Elizabeth; Petkovic, Grace; Rounis, Elisabeth; Cheng, Fan; Sipkova, Zuzana; Waters, Patrick; Hornby, Stella; Hofer, Monika; Isabel Leite, M
Abstract : We present the case of a 46-year-old Caucasian woman, who developed seronegative necrotizing myositis (with elevated creatine kinase [CK, 54 000]) whilst on tamoxifen treatment following remission of breast carcinoma (Grade II mucinous, solid papillary and ductal breast carcinoma), which was treated six months previously with surgery and adjuvant radiotherapy. The necrotizing myositis was initially treated successfully with prednisolone. However, on prednisolone cessation, she represented with myositis, which required steroid therapy again. Within two weeks, patient developed acute loss of vision in the left eye, which deteriorated to counting fingers over days, leading to the diagnosis of severe left optic neuritis. Serum positivity for Aquaporin-4 antibodies confirmed a diagnosis of neuromyelitis optica spectrum disease (NMOSD). The patient had no other relevant past medical history or co-morbidities, namely other organ-specific or systemic autoimmune manifestations. She was treated with intravenous steroids and plasma exchange, but she did not recover her vision. She continues on immune therapy and her three pathologies remain stable. Previous case reports have noted possible associations of NMOSD with myositis and others with malignancies, including breast cancer. Our case illustrates that NMOSD may be, very rarely, associated with, or preceded by, necrotizing myositis and may also be a paraneoplastic presentation.